The relationship between perceived stress and postpartum depression through the mediating role of marital satisfaction in postpartum women - Bahareh Mohammadian; Saeed Bakhtiarpour; Farah Naderi; Zahra Dasht Bozorgi (Journal of Research Development in Nursing and Midwifery)
Background: Postpartum depression (PPD) is a significant mental health concern affecting many women worldwide. While various factors contribute to PPD, the role of perceived stress and marital satisfaction remains underexplored. This research aimed to investigate the mediating role of marital satisfaction in the relationship between perceived stress and PPD among postpartum women in Ahvaz. Methods: A cross-sectional study utilizing structural equation modeling examined the relationships among perceived stress, marital satisfaction, and PPD. A convenience sample of 319 postpartum women who visited healthcare centers in Ahvaz, southern Iran, in 2023 was recruited. Data were collected using the Edinburgh Postnatal Depression Scale, the Perceived Stress Scale, and the Marital Satisfaction Scale. Data analysis was performed using structural equation modeling with SPSS-26 and AMOS-26 software. Results: The findings indicated a significant negative correlation between perceived stress and marital satisfaction (β = -0.45, P < 0.001). Both marital satisfaction (β = -0.31, P = 0.008) and perceived stress (β = 0.20, P = 0.028) were significantly related to PPD. Bootstrapping results also confirmed a significant indirect effect of perceived stress on PPD via marital satisfaction (β = 0.17, P = 0.027). Conclusion: The interplay between perceived stress, marital satisfaction, and PPD is complex and multifaceted. This research highlights the potential importance of marital satisfaction as a critical factor in understanding the pathway between stress and PPD. Future interventions might consider incorporating strategies to enhance marital quality to reduce the risk of PPD.